Assessment of systemic inflammation by time‐trends of blood granulocyte count and plasma myeloperoxidase and elastase concentrations following colic surgery in horses. Issue 4 (4th May 2016) - Salciccia, Alexandra; Grulke, Sigrid; de la Rebière de Pouyade, Geoffroy; Franck, Thierry; Detilleux, Johann; Serteyn, Didier; Sandersen, Charlotte
Abstract: Objective: To determine changes in blood granulocyte counts and in plasma myeloperoxidase (MPO) and elastase (ELT) concentrations in surgical colic cases, and to determine the relationship between these changes and the surgical procedure performed, occurrence of postoperative ileus, and final outcome. Design: Prospective clinical study conducted over a 12‐month period. Setting: University teaching hospital. Animals: Fifty‐three horses undergoing emergency laparotomy and surviving at least 12 hours postoperatively. Interventions: Blood samples were taken before surgery, during surgery, at the recovery from anesthesia, and then serially until the 150th hour after the first blood sampling. Granulocyte counts were performed by an automated cell hematology analyzer. Specific ELISAs were performed for the MPO and ELT measurements. Mixed models were used to compare the time‐trends of the 3 parameters. Measurements and Main Results: Taking all horses together, the time‐trends of MPO and ELT were not significantly different from each other, but they were significantly different from the granulocyte time‐trend. The type of surgical procedure did not influence the time‐trends of the 3 parameters. Significant changes in the granulocyte time‐trends were associated with postoperative ileus and outcome. Significant changes in the MPO time‐trends were associated with outcome. The ELT time‐trends were not influenced by ileus or outcome. Conclusions: Granulocyte counts and MPO change over time and are related to the severity of the inflammatory reaction in surgical colic cases. These time‐trends may allow evaluation of treatment efficacy in an effort to modulate excessive granulocyte activation and degranulation.